Building a semiotic repertoire for social action: interactional competence as biographical discovery. Issue 1 (2nd January 2018) - Eskildsen, Søren W.
Abstract: This commentary draws on the four articles in this issue to discuss interactional competence from a usage-based perspective. The usage-based conception of language knowledge as an inventory of form-meaning pairings used for communicative purposes will be qualified by incorporating the idea that these communicative purposes are social actions. L2 learning is a matter of biographical discovery in which the accomplishment of social actions is the driving force and L2 teaching should revolve around semiotic resources for accomplishing these. I conclude by calling for further usage-based L2 research that builds on and advances a view of language as a tool for social action.